La experiencia de Dios en el Nuevo Estado. Militarización y fascistización de la Semana Santa, 1936-1945 - César Rina Simón (Amnis)
The festivities associated with « popular » religiosity play an important role through the representation of symbols, discourses, and social identities that were used by the different ideological factions to their convenience. The National Catholicism used these rituals and religious context to legitimize the dictatorship in accordance with divine principles. The Francoist imaginary focuses on appropriating and redefining the symbols associated with the « popular » religiosity, from a purifying ecclesiastical perspective or fascist rhetoric.